The role of natural killer cells in chronic myeloid leukemia - Danier, Anna Carolyna Araújo (Associação Brasileira de Hematologia e Hemoterapia, 2011)
Chronic myeloid leukemia is a neoplasia resulting from a translocation between chromosomes 9 and 22 producing the BCR-ABL hybrid known as the Philadelphia chromosome (Ph). In chronic myeloid leukemia a proliferation of malignant myeloid cells occurs in the bone marrow due to excessive tyrosine kinase activity. In order to maintain homeostasis, natural killer cells, by means of receptors, identify the major histocompatibility complex on the surface of tumor cells and subsequently induce apoptosis. The NKG2D receptor in the natural killer cells recognizes the transmembrane proteins related to major histocompatibility complex class I chain-related genes A and B (MICA and MICB), and it is by the interaction between NKG2D and MICA that natural killer cells exert cytotoxic activity against chronic myeloid leukemia tumor cells. However, in the case of chronic exposure of the NKG2D receptor, the MICA ligand releases soluble proteins called sMICA from the tumor cell surface, which negatively modulate NKG2D and enable the tumor cells to avoid lysis mediated by the natural killer cells. Blocking the formation of sMICA may be an important antitumor strategy. Treatment using tyrosine kinase inhibitors induces modulation of NKG2DL expression, which could favor the activity of the natural killer cells. However this mechanism has not been fully described in chronic myeloid leukemia. In the present study, we analyze the role of natural killer cells to reduce proliferation and in the cellular death of tumor cells in chronic myeloid leukemia.